Womanpower in the 1960's, Fabian Feminism. - Beals, Polly (2009)
Worked on book about Fabian feminism. Finished the final chapter but book isn't complete yet. Wrote and delivered paper in London in March 2009. Is expanding book to include 1980's and 1990's Fabian feminism.
Keywords: dept.his; faculty_collection; sabbatical_report

The System: The American Constitution in Historical Perspective 1763-1929 - Gerber, Richard A. (Cengage Learning, 2009)
Keywords: United States; United States. Constitution; Constitutional history; dept.his; faculty_collection

Playing the feminine card: Women of the early modern map trade - Petto, C.M. (Cartographica, 2009)
Images of allegorical women have often appeared on maps or in atlas frontispieces as objects in need of security provided by male protectors or as the counterpoint, objects to be dominated by male possessors. Exploring the role of women in the early modern map trade initially reveals not only a similar male dominance but also similar calls for protection. Nearly 10 years ago, Alice Hudson and Mary McMichael Ritzlin produced a checklist of about 300 pre-twentieth-century women in cartography. The present work contributes to the further investigation of some of these women in the early modern map trade and studies in the allied field of book printing, and more general works on women in commercial trade provide the framework for this piece. Women in the map trade were quite cognizant of the challenges of their gender and used a feminine discourse-that is, they played the feminine card-when it served their interests. All of these women, however, participated in the male discourse of the corporate community, which entailed not only making contracts and partnerships and advertising and producing new works but also making use of the social network within the trade, as well as exploiting the patronage connections cultivated by their husbands before them.
5 citations (Crossref) [2023-10-31]
Keywords: Angleterre; England; France; commerce de l'impression des cartes; dept.his; engravers; femmes; graveurs; image; map publishers; map-printing trade; women; éditeurs cartographiques

The great industrial war: Framing class conflict in the media, 1865-1950 - Rondinone, T. (Rutgers University Press, 2009)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers.Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported. copyright © 2010 by Troy Rondinone All rights reserved.
Journal Abbreviation: The Gt. Indust. War: Framing Cl. Confl ict in the Media, 1865-1950 Pages: 247 Publication Title: The Gt. Indust. War: Framing Cl. Confl ict in the Media, 1865-1950
Keywords: dept.his

South African territorial segregation: new data on African farm purchases, 1913-1936 - Feinberg, Harvey M; Horn, Andre C (The Journal of African History, 2009)
By using new sources and a complementary historical and geo-analytical approach, this article Illustrates that the Natives Land Act (no. 27 of 1913) failed to stop Africans from buying land. New evidence demonstrates that African land ownership outside the reserves in the Transvaal actually increased after 1913. This evidence leads to a deeper questioning of the extent to which the South African government was able to impose rural territorial segregation by 1936 and reveals the limits of white power in the early Union period.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-862-260-598-682 tex.type: [object Object]
Keywords: Archives; Land; Law; Race; South Africa; apartheid; dept.his; historical geography; land tenure; landownership; legislation; racial segregation

Semblance of Sovereignty: Cartographic Possession in Map Cartouches and Atlas Frontispieces of Early Modern Europe - Petto, Christine M. (Symbolic Landscapes, 2009)
Maps always present an interpretation of reality and always carry distortions, some of which are consciously or unconsciously ideological. The geographicity of mapping, which involves an intertwining of both science and art, is a vehicle for spatialized/spatializing interpretations of an actual spatiality, and as such is a catalyst for enacting further spatial productions on the basis of the capacity of maps to project themselves “into the landscape.” The scientific pretensions of mapping serve to veil the character of their projective enactment. Maps always entail virtual embodiment, that is, maps realize one possibility out of many, even in the most mathematically “accurate” of spatial relations. Thus, if the imaginative involves both embodied schema and virtual embodiments, we cannot dismiss the role of the geography of imagination in a dialectical relation with the geography of perception, of the actual. The symbolic function of cartouches and frontispieces provides an imagineering context of constructing reality on the basis of the symbolization.
Citation Key Alias: lens.org/078-762-124-744-708
Keywords: Facsimile Edition; Manuscript Library; Online Collection; United Province; Virtual Embodiment; dept.his

Guarding the switch: cultivating nationalism during the pullman strike - Rondinone, Troy (The Journal of the Gilded Age and Progressive Era, 2009)
The Pullman Strike of 1894 was a cataclysmic event for the nation. During its violent course, the print media provided an interpretive frame that portrayed the strike in large measure as an immigrant-inspired attack on American laws and democratic customs. Often characterizing the strikers as “foreigners” in the thrall of anarchist ideologies and a tyrannous labor chieftain, journalists painted a stark picture indeed. Employing framing theory, Gramsci's notion of hegemony, and recent insights on the ethnic quality of nationalism, this essay argues that newspapers and other major print periodicals significantly contributed to the formation of nationalist attitudes at a time when many Americans were deeply worried over the direction in which the country was headed. © 2009, Society for Historians of the Gilded Age and Progressive Era. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-980-600-754-189 tex.type: [object Object]
Keywords: dept.his